Highly Sensitive and Accurate Assessment of Minimal Residual Disease in Chronic Lymphocytic Leukemia Using the Novel CD160-ROR1 Assay - Farren, Timothy W.; Sadanand, Kaushik S.; Agrawal, Samir G. (Frontiers in Oncology, 2020)
Minimal residual disease (MRD) negativity in Chronic Lymphocytic Leukaemia (CLL) has a favourable prognostic outcome compared with MRD positivity. This study investigated a flow cytometric assay (CD160-ROR1FCA) targeting the tumour-specific antigens CD160 and receptor tyrosine kinase-like orphan receptor 1 (ROR1), along with CD2, CD5, CD19, CD45. CD160-ROR1FCA was compared with the 8-colour European Research Initiative for CLL (ERIC) gold-standard assay for CLL MRD detection. CD160-ROR1FCA had a limit of detection of 0.001% and showed strong correlation with ERIC (R=0.98, p<0.01) with negligible differences in MRD detection (bias -0.3152 95%CI 5.586 to -6.216). Using CD160-ROR1FCA, increased expression of both CD160 and ROR1 was found in Monoclonal B cell Lymphocytosis compared to low-level polyclonal B-cell expansions (p<0.01). Patients in CR and MRD negative had a longer EFS (not reached) than those in CR but MRD positive (756 days, p<0.01) versus 113 days in patients with partial remission (p<0.01). Patients with MRD levels of >0.01% to 0.1% had a longer EFS (2333 days), versus levels between 0.1% to 1% (1049 days). CD160-ROR1FCA offers advantages over the ERIC methodology, in terms of cost, a simple gating strategy, speed of analysis, with small volume samples and is an alternative for routine CLL MRD detection.